Pharmacological Advancements in the Management of Constipation-Predominant Irritable Bowel Syndrome: A Comprehensive Review - Khaled Jadallah; Roberto De Giorgio; Rami Jadallah (Medical Science: Trends and Innovations Vol. 4, 2025)
Irritable bowel syndrome (IBS) is a complex disorder of gut-brain interaction (DGBI). It affects a diverse population across various age groups and ethnicities. IBS is a common medical disorder worldwide, with reported prevalence rates ranging from 5% to 35%. Patients diagnosed with IBS often experience significant disruptions in their daily activities and a diminished quality of life, which can be attributed to the limited effectiveness of conventional treatment options. Additionally, the long-term consequences of the condition may give rise to psychological challenges, potentially resulting in polypharmacy or the concurrent use of multiple medications. This scenario presents inherent risks, including the possibility of drug interactions, a decline in overall health, and increased healthcare costs. The symptoms of IBS may include abdominal pain and bloating, frequently associated with visceral hypersensitivity and psychological factors, along with diarrhea, constipation, or a combination of these bowel patterns. In accordance with the Rome IV criteria, IBS is classified based on different types of bowel patterns. There are four recognized subtypes of IBS: IBS with constipation (IBS-C), IBS with diarrhea (IBS-D), mixed IBS (IBS-M), and unsubtyped IBS (IBS-U). This classification system facilitates the accurate diagnosis and effective management of the condition. The IBS-C subtype affects a significant number of patients, particularly older adults and those from lower socioeconomic backgrounds. Recent studies indicate that IBS-C is linked to higher levels of functional impairment compared to other subtypes of IBS. Conventional pharmacological and non-pharmacological treatment options for IBS-C have limited effectiveness and may cause significant adverse effects. This results in higher long-term healthcare costs. Over the past few decades, the ineffectiveness in treating patients with IBS-C has largely stemmed from a poor understanding of the disease’s pathophysiology, a failure to consider the patient as a whole, and inappropriate patient selection and treatment endpoints in clinical trials. Over the past two decades, significant advancements have been made in the development of effective and safer pharmacologic treatments for IBS-C. These advancements are grounded in an enhanced understanding of the pathophysiological mechanisms underlying IBS-C and the introduction of medications that demonstrate increased selectivity within established pharmacologic classes recognized for their efficacy. This narrative review aims to provide a comprehensive overview of the available treatment options for IBS-C, highlighting their mechanisms of action, as well as their efficacy and safety profiles as determined by pertinent clinical trials. The review commences with a summary of laxative-based therapies and subsequently offers an up-to-date evaluation of four distinct classes of medications: prokinetics, prosecretory agents, bile acid modulators, and tenapanor.